Dual‐Targeting Peptides RGD10‐NGR9‐Conjugated Lanthanide Nanoparticle@Polydopamine as Upconversion Nanoprobes for In Vivo Imaging of Lung Cancer. Issue 12 (29th September 2020) - Cao, Jingxue; Zhang, Li; Ding, Xi; Liu, Di; Su, Bo; Shi, Jingyun
Abstract: Near‐infrared (NIR) fluorescence‐guided surgery is a developing field in precision medicine for cancer treatment. However, traditional NIR fluorescent reagents have limitations including lower sensitivity and specificity for tumor delineation, as well as insufficient photostability and tissue penetration depth. Herein, an improved dual‐targeting lanthanide‐doped NIR‐to‐visible upconversion nanoprobe is constructed for fluorescent imaging of lung cancer. The nanoprobes (UCNP@P‐RGD‐NGR) are synthesized by preparing polydopamine‐coated NaYF4 :Yb/Tm@NaYF4 upconversion nanoparticles (UCNP) and conjugating them with dual‐targeting peptides RGD10‐NGR9, which are designed to target both integrin αvβ3/αvβ5 and aminopeptidase N receptors on tumor cells. The monodispersed core–shell nanoprobe is rod‐shaped (≈32 nm in minor axis) with ultrathin polydopamine shell (≈2 nm) under transmission electron microscopy. The absorption spectrum and upconversion luminescence properties of the nanoprobes are identified by spectrometry. Toxicity analysis on cellular and animal experiments suggests the nanoprobes are well biocompatible. UCNP@P‐RGD‐NGR can specifically target A549 cancer cells as revealed by competitive cell binding assay and ICP‐MS. Imaging studies in vivo with BALB/c nude mice bearing tumor xenografts demonstrate that UCNP@P‐RGD‐NGR can delineate tumor from surrounding normal tissues with strong upconversion blue–violet luminescence. This dual‐targeting nanoprobe shows great potential for clinical application for NIR fluorescence surgical navigation of lung cancer. Abstract : Compared with single‐targeting peptides RGD or NGR, a CC cyclic dual‐targeting peptide RGD10‐NGR9 can significantly enhance its specificity of tumor vascular system with high expression of integrin αvβ3/αvβ5 or APN receptors. In this paper, the dual‐targeting peptides are conjugated with polydopamine‐coated NaYF4 :Yb/Tm@NaYF4 upconversion nanoparticles to construct highly specific tumor‐ targeting upconversion nanoprobes for near‐infrared fluorescence‐guide surgery of lung cancer.